Effect of the Ozone Application in the Nutrient Solution and the Yield and Oxidative Stress of Hydroponic Baby Red Chard - Alejandra Machuca Vargas; Ana Cecilia Silveira Gómez; Cristian Hernández-Adasme; Víctor Hugo Escalona Contreras (Horticulturae, 2023)
Novel ozone (O3) sanitizing treatments can be used to decrease the microbial load during cultivation, but they would affect the composition of the nutrient solution. Variations in the nutrient composition decrease crop yields, especially if a strong oxidizing agent such as ozone is used. In this study, O3 was applied throughout the culture every two days at doses of 0.0 (control); 0.5; 1.0; and 2.0 mg·L−1 for 3 min on baby red chard (Beta vulgaris L. cv. SCR 107) grown in a floating hydroponic system. Macronutrients and micronutrients in the nutrient solution, yield, antioxidant compounds, and oxidative stress enzymes were evaluated in plants. Macronutrients in the nutrient solution were not affected by O3, whereas micronutrients, such as Fe and Mn, decreased by 88.2 and 39.6%, respectively, at the 0.5 mg·L−1 dose. The dose of 0.5 mg·L−1 produced more fresh matter and leaf area than the control. Antioxidant capacity and total phenols were not significantly affected by O3 treatments; however, higher SOD, CAT, and APX activity after O3 applications were found. It is concluded that ozone applications to the nutrient solution affect the availability of some micronutrients and increase oxidative stress and yield in baby red chard plants.